Deep learning approach for genetic selection of stress response in the Amazon fish Colossoma macropomum - Celma G. Lemos; Baltasar F. Garcia; Marcelo S.S. Filho; Jairo R. Arango; Arno J. Butzge; Luciana Shiotsuki; Luiz Eduardo L. Freitas; Fabrício P. Rezende; Elisabeth C. Urbinati; Guilherme J.M. Rosa; Diogo T. Hashimoto (Aquaculture, 2025)

Recent advancements in aquaculture genetics - José M. Yáñez; Roberto Neira; Diogo T. Hashimoto; Delphine Lallias; Peng Xu; Dean R. Jerry (Aquaculture, 2025)

Spatiotemporal dynamics of bioproduction systems and ecosystem services in the Baroro and Pagsanjan-Lumban watersheds, Philippines - Nico R. Almarines; Shizuka Hashimoto; Juan M. Pulhin; Canesio D. Predo.; Florencia B. Pulhin; Angelica T. Magpantay; Osamu Saito (Paddy and Water Environment, 2025)

Thermoacoustic parametric instability of premixed ammonia flames propagating downwards in an open-closed tube - Jerric R. Delfin; Feng Guo; Nozomu Hashimoto; Osamu Fujita (Fuel, 2024)

Gene-associated markers as a genomic and transcriptomic resource for a highly migratory and apex predator shark (Isurus oxyrinchus) - Rodrigo R. Domingues; Vito Antonio Mastrochirico-Filho; Natalia J. Mendes; Diogo T. Hashimoto; Rui Coelho; Agostinho Antunes; Fausto Foresti; Fernando F. Mendonça (Marine Biology, 2022)

The future of artificial intelligence in the context of industrial ecology - Franco Donati; Sébastien M. R. Dente; Chen Li; Xaysackda Vilaysouk; Andreas Froemelt; Rohit Nishant; Gang Liu; Arnold Tukker; Seiji Hashimoto (Journal of Industrial Ecology, 2022)
Artificial intelligence (AI) applications and digital technologies (DTs) are increasingly present in the daily lives of citizens, in cities and in industries. These developments generate large amounts of data and enhance analytical capabilities that could benefit the industrial ecology (IE) community and sustainability research in general. With this communication, we would like to address some of the opportunities, challenges, and next steps that could be undertaken by the industrial ecology community in this realm. This article is an adapted summary of the discussion held by experts in industrial ecology, AI, and sustainability during the 2021 Industrial Ecology Day conference session titled “The Future of Artificial Intelligence in the Context of Industrial Ecology.” In brief, building on previous studies and communications, we advise the industrial ecology community to: (1) create internal committees and working groups to monitor and coordinate AI applications within and outside the community; (2) promote and ensure transdisciplinary efforts; (3) determine optimal infrastructure and governance of AI for IE to minimize undesired effects; and (4) act on effective representation and on reduction of digital divides.

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Total environmental impacts of Japanese material production - Chika Aoki‐Suzuki; Sébastien M. R. Dente; Daisuke Tanaka; Chihiro Kayo; Shinsuke Murakami; Chiharu Fujii; Kiyotaka Tahara; Seiji Hashimoto (Journal of Industrial Ecology, 2021)
Decoupling well‐being from resource use and its associated environmental impacts through resource efficiency and circular economy has become the mainstream agenda for sustainable development. Resource productivity and material flow indicators have been widely used to evaluate resource decoupling. Several approaches have been introduced in Europe to calculate the life cycle environmental impact of resource use at the macro‐level and assess impact decoupling. However, no studies have been conducted to estimate the overall aggregated environmental impact (total environmental impact) associated with resource use in all resource categories using statistical data at the national level and life cycle inventory databases in Japan. This study is the first assessment of the total environmental impact at the national level in Japan, particularly addressing the production process for 213 materials. The study makes it possible to distinguish the 4 phases for environmental impact generation (foreign supply chain, domestic supply chain, production process, and use), 12 environmental impact areas, and the resource category (biomass, fossil, metal, and non‐metallic mineral) of each material. The study shows that there is a higher impact generated by production and foreign supply chain phases in biomass and fossil resources such as crops, livestock, dairy products, and petroleum and coal products as well as some metals (steel and copper). These results imply that measures to reduce resource use and improve energy efficiency in direct production and foreign supply chains through local resource procurement and further resource‐efficient approaches, including the circular economy, should be prioritized for Japan, with its resource‐scarce and manufacturing‐oriented economy.

Altered Notch Signaling in Developing Molar Teeth of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Deficient Mice - B. D. Fulop; B. Sandor; E. Szentleleky; E. Karanyicz; D. Reglodi; B. Gaszner; R. Zakany; H. Hashimoto; T. Juhasz; A. Tamas (Journal of Molecular Neuroscience, 2019)

High‐resolution mapping of daily climate variables by aggregating multiple spatial data sets with the random forest algorithm over the conterminous United States - Hirofumi Hashimoto; Weile Wang; Forrest S. Melton; Adam L. Moreno; Sangram Ganguly; Andrew R. Michaelis; Ramakrishna R. Nemani (International Journal of Climatology, 2019)
High‐resolution gridded climate data products are crucial to research and practical applications in climatology, hydrology, ecology, agriculture, and public health. Previous works to produce multiple data sets were limited by the availability of input data as well as computational techniques. With advances in machine learning and the availability of several daily satellite data sets providing unprecedented information at 1 km or higher spatial resolutions, it is now possible to improve upon earlier data sets in terms of representing spatial variability. We developed the NEX (NASA Earth Exchange) Gridded Daily Meteorology (NEX‐GDM) model, which can estimate the spatial pattern of regional surface climate variables by aggregating several dozen two‐dimensional data sets and ground weather station data. NEX‐GDM does not require physical assumptions and can easily extend spatially and temporally. NEX‐GDM employs the random forest algorithm for estimation, which allows us to find the best estimate from the spatially continuous data sets. We used the NEX‐GDM model to produce historical 1‐km daily spatial data for the conterminous United States from 1979 to 2017, including precipitation, minimum temperature, maximum temperature, dew point temperature, wind speed, and solar radiation. In this study, NEX‐GDM ingested a total of 30 spatial variables from 13 different data sets, including satellite, reanalysis, radar, and topography data. Generally, the spatial patterns of precipitation and temperature produced were similar to previous data sets with the exception of mountain regions in the western United States. The analyses for each spatially continuous data set show that satellite and reanalysis led to better estimates and that the incorporation of satellite data allowed NEX‐GDM to capture the spatial patterns associated with urban heat island effects. The NEX‐GDM data is available to the community through the NEX data portal.

Endovascular Biopsy: In Vivo Cerebral Aneurysm Endothelial Cell Sampling and Gene Expression Analysis - Daniel L. Cooke; David B. McCoy; Van V. Halbach; Steven W. Hetts; Matthew R. Amans; Christopher F. Dowd; Randall T. Higashida; Devon Lawson; Jeffrey Nelson; Chih-Yang Wang; Helen Kim; Zena Werb; et al. (Translational Stroke Research, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.

Lead line in rodents: an old sign of lead intoxication turned into a new method for environmental surveillance - Fellipe Augusto Tocchini de Figueiredo; Junia Ramos; Erika R. Hashimoto Kawakita; Alina S. Bilal; Frederico B. de Sousa; William D. Swaim; Joao P. Mardegan Issa; Raquel F. Gerlach (Environmental Science and Pollution Research, 2016)

Effects of the potential lithium-mimetic, ebselen, on brain neurochemistry: a magnetic resonance spectroscopy study at 7 tesla - Charles Masaki; Ann L. Sharpley; Beata R. Godlewska; Adam Berrington; Tasuku Hashimoto; Nisha Singh; Sridhar R. Vasudevan; Uzay E. Emir; Grant C. Churchill; Philip J. Cowen (Psychopharmacology, 2016)

Triassic–Jurassic granites on the Lord Howe Rise, northern Zealandia - N. Mortimer; R. E. Turnbull; J. M. Palin; A. J. Tulloch; N. Rollet; T. Hashimoto (Australian Journal of Earth Sciences, 2015)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

Structural and Morphometric Comparison of the Molar Teeth in Pre-eruptive Developmental Stage of PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; Sz. Felszeghy; T. Juhasz; D. Reglodi; L. Mark; P. Kiss; A. Jungling; B. D. Fulop; A. D. Nagy; H. Hashimoto; R. Zakany; et al. (Journal of Molecular Neuroscience, 2014)

Examination of Calcium-Binding Protein Expression in the Inner Ear of Wild-Type, Heterozygous and Homozygous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Knockout Mice in Kanamycin-Induced Ototoxicity - A. Nemeth; K. Szabadfi; B. Fulop; D. Reglodi; P. Kiss; J. Farkas; B. Szalontai; R. Gabriel; H. Hashimoto; A. Tamas (Neurotoxicity Research, 2014)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

Comparative Examination of Inner Ear in Wild Type and Pituitary Adenylate Cyclase Activating Polypeptide (PACAP)-Deficient Mice - A. Tamas; K. Szabadfi; A. Nemeth; B. Fulop; P. Kiss; T. Atlasz; R. Gabriel; H. Hashimoto; A. Baba; N. Shintani; Zs. Helyes; D. Reglodi (Neurotoxicity Research, 2012)

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Evaluating the impacts of climate and elevated carbon dioxide on tropical rainforests of the western Amazon basin using ecosystem models and satellite data - HIROFUMI HASHIMOTO; FORREST MELTON; KAZUHITO ICHII; CRISTINA MILESI; WEILE WANG; RAMAKRISHNA R. NEMANI (Global Change Biology, 2010)
Forest inventories from the intact rainforests of the Amazon indicate increasing rates of carbon gain over the past three decades. However, such estimates have been questioned because of the poor spatial representation of the sampling plots and the incomplete understanding of purported mechanisms behind the increases in biomass. Ecosystem models, when used in conjunction with satellite data, are useful in examining the carbon budgets in regions where the observations of carbon flows are sparse. The purpose of this study is to explain observed trends in normalized difference vegetation index (NDVI) using climate observations and ecosystem models of varying complexity in the western Amazon basin for the period of 1984–2002. We first investigated trends in NDVI and found a positive trend during the study period, but the positive trend in NDVI was observed only in the months from August to December. Then, trends in various climate parameters were calculated, and of the climate variables considered, only shortwave radiation was found to have a corresponding significant positive trend. To compare the impact of each climate component, as well as increasing carbon dioxide (CO 2 ) concentrations, on evergreen forests in the Amazon, we ran three ecosystem models (CASA, Biome‐BGC, and LPJ), and calculated monthly net primary production by changing a climate component selected from the available climate datasets. As expected, CO 2 fertilization effects showed positive trends throughout the year and cannot explain the positive trend in NDVI, which was observed only for the months of August to December. Through these simulations, we demonstrated that the positive trend in shortwave radiation can explain the positive trend in NDVI observed for the period from August to December. We conclude that the positive trend in shortwave radiation is the most likely driver of the increasing trend in NDVI and the corresponding observed increases in forest biomass.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Constraining rooting depths in tropical rainforests using satellite data and ecosystem modeling for accurate simulation of gross primary production seasonality - KAZUHITO ICHII; HIROFUMI HASHIMOTO; MICHAEL A. WHITE; CHRISTOPHER POTTER; LUCY R. HUTYRA; ALFREDO R. HUETE; RANGA B. MYNENI; RAMAKRISHNA R. NEMANI (Global Change Biology, 2007)
Accurate parameterization of rooting depth is difficult but important for capturing the spatio‐temporal dynamics of carbon, water and energy cycles in tropical forests. In this study, we adopted a new approach to constrain rooting depth in terrestrial ecosystem models over the Amazon using satellite data [moderate resolution imaging spectroradiometer (MODIS) enhanced vegetation index (EVI)] and Biome‐BGC terrestrial ecosystem model. We simulated seasonal variations in gross primary production (GPP) using different rooting depths (1, 3, 5, and 10 m) at point and spatial scales to investigate how rooting depth affects modeled seasonal GPP variations and to determine which rooting depth simulates GPP consistent with satellite‐based observations. First, we confirmed that rooting depth strongly controls modeled GPP seasonal variations and that only deep rooting systems can successfully track flux‐based GPP seasonality at the Tapajos km67 flux site. Second, spatial analysis showed that the model can reproduce the seasonal variations in satellite‐based EVI seasonality, however, with required rooting depths strongly dependent on precipitation and the dry season length. For example, a shallow rooting depth (1–3 m) is sufficient in regions with a short dry season (e.g. 0–2 months), and deeper roots are required in regions with a longer dry season (e.g. 3–5 and 5–10 m for the regions with 3–4 and 5–6 months dry season, respectively). Our analysis suggests that setting of proper rooting depths is important to simulating GPP seasonality in tropical forests, and the use of satellite data can help to constrain the spatial variability of rooting depth.

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Effect of p-Nonylphenol on sperm motility in Japanese medaka (Oryzias latipes) - R. Kawana; C.A. Strüssmann; S. Hashimoto (Fish Physiology and Biochemistry, 2003)

Retrolyc1 subfamilies defined by different U3 LTR regulatory regions in the Lycopersicon genus - P. Araujo; J. Casacuberta; A. Costa; R. Hashimoto; M.-A. Grandbastien; M.-A. Van Sluys (Molecular Genetics and Genomics, 2001)

In vitro characterization of J-113397, a non-peptide nociceptin/orphanin FQ receptor antagonist - R. Bigoni; G. Calo'; A. Rizzi; R. Guerrini; C. De Risi; Y. Hashimoto; E. Hashiba; D.G. Lambert; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

A major metabolite of aceclofenac, 4′-hydroxy aceclofenac, suppresses the production of interstitial pro-collagenase/proMMP-1 and pro-stromelysin-1/proMMP-3 by human rheumatoid synovial cells - R. Yamazaki; S. Kawai; Y. Mizushima; T. Matsuzaki; S. Hashimoto; T. Yokokura; A. Ito (Inflammation Research, 2000)

Mangrove-saltmarsh dynamics on a bay-head delta in the Hawkesbury River estuary, New South Wales, Australia - N. Saintilan; T. R. Hashimoto (Hydrobiologia, 1999)

Mixture in the distribution of haloperidol-induced oral dyskinesias in the rat supports an animal model of tardive dyskinesia - Takeshi Hashimoto; David E. Ross; Xue-Min Gao; Deborah R. Medoff; C. A. Tamminga (Psychopharmacology, 1998)

Anti-inflammatory effect of YPE-01, a novel diarylheptanoid derivative, on dermal inflammation in mice - R. Yamazaki; R. Aiyama; T. Matsuzaki; S. Hashimoto; T. Yokokura (Inflammation Research, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Molecular phylogeny of vestimentiferans collected around Japan, revealed by the nucleotide sequences of mitochondrial DNA - S. Kojima; R. Segawa; J. Hashimoto; S. Ohta (Marine Biology, 1997)